Comparison of diagnostic image modalities for the detection of Achilles tendon tendinopathy using ankle magnetic resonance imaging - Lee, Joohyun; Lee, Jee Young; Kang, Keum Nae; Park, Soyoon; Jang, Jae Ni; Park, Sukhee; Kim, Young Uk (Frontiers in Physiology, 2025)
BackgroundA thickened Achilles tendon (AT) is one of the important morphological changes observed in Achilles tendinopathy (ATTP). Previous research studies have demonstrated that both Achilles tendon thickness (ATT) and Achilles tendon cross-sectional area (CSA) (ATCSA) are correlated with ATTP in subjects. However, the comparative value of ATT and ATCSA in relation to ATTP is not clear, and no studies have calculated the optimal clinical threshold values of ATT and ATCSA. The goal of this research was to assess ATT and ATCSA and determine which parameter is more sensitive in predicting ATTP.MethodsAT lesions were studied in 31 subjects with ATTP and 36 asymptomatic subjects who underwent ankle magnetic resonance imaging (A-MRI) and showed no evidence of ATTP. Axial T1-weighted A-MRI images were obtained at the AT level. We measured the ATT and ATCSA at the junction of the soleus and gastrocnemius aponeurosis using an image analysis program. The ATT was defined as the thickest point at the AT margin. The ATCSA was defined as the total cross-sectional area of the AT at the region showing the most pronounced inflammatory lesions. In addition, a subgroup analysis by sex was performed to evaluate the gender-specific diagnostic performance of ATT and ATCSA.ResultsThe average ATT was 3.83 ± 0.76 mm in the control group and 5.42 ± 0.97 mm in the ATTP group. The average ATCSA was 46.49 ± 7.12 mm2 in the control group and 82.59 ± 29.71 mm2 in the ATTP group. ATTP subjects had significantly higher ATT (p < 0.001) and ATCSA (p < 0.001) than the control subjects. ROC curve analysis showed that the optimal threshold value of the ATCSA was 57.20 mm2. The responsiveness of ATCSA was 87.1%, and its precision was 88.9%. The optimal threshold value of the ATT was 4.64 mm. The responsiveness of ATT was 80.6%, and its precision was 80.6%. We compared the area under the curve (AUC) for two analyzed diagnostic methods. The ATCSA’s AUC is 0.95 (95% CI: 088–1.00), and the ATT’s AUC is 0.91 (95% CI: 0.84–0.97).ConclusionAlthough both ATCSA and ATT were significantly correlated with ATTP, the ATCSA was a more sensitive measurement parameter.